Descrição dos diferentes estágios do desenvolvimento embrionário de aves das ordens Anseriformes, Galliformes e Psittaciformes e sua aplicação no embriodiagnóstico de espécies selvagens - Guida, Fernanda Junqueira Vaz (2018)
Although the artificial incubation of wild-bird eggs has progressed in the last decades, this tool is still rudimentary when compared to the technology applied in the poultry industry, which presented considerable advances in order to maximize eggs hatchability. To wild species, parameters such as temperature and humidity of the incubator are often determined by trial and error, taking into account only the hatching rate of the incubated eggs. In this sense, the information generated by embryodiagnosis is of great value in the incubation of unconventional eggs because they offer a greater detail on the causes of birth failure (egg infertility, transport, storage, age and reproductive nutrition, etc.). Thus, the present study aimed to describe the different stages of the embryonic development of representatives of the Anseriformes, Galliformes and Psittaciformes orders of the species Cygnus atratus, Pavo cristatus and Nymphicus hollandicus, respectively. The eggs were incubated at a standard temperature and humidity for each species and, to describe the development, embryos with less than 50% of the incubation period were euthanized by hyportemia and, above this period, by anesthetic overdose using the Halothane 100% inhalant liquid. In total, 238 eggs were incubated, but due to the natural deaths during the incubation process, 67 embryos were described so far, with the final two thirds of the incubation period prioritized. Due to the difficulty in acquiring viable eggs and the reduced number of embryos per day of incubation, the development picture presented gaps, so the research will continue. We believe the continuity of this study will provide subsidies for the improvement of techniques of artificial incubation of eggs, an indispensable instrument in programs of conservation of several species of wild birds.